Thyroid surgery : preventing and managing complications - Miccoli, P. (Paolo) (Oxford : Wiley-Blackwell, 2013)
This book helps endocrine surgeons, general surgeons, and otolaryngologists perfect surgical techniques and overcome the various complications that can arise when performing surgery of the thyroid.
Front Matter -- Epidemiology and Acceptable Rates of Complications Following Thyroid and Parathyroid Surgery. Incidence of Morbidity Following Thyroid Surgery / Paolo Miccoli, Michele N Minuto, Mario Miccoli -- Medical Malpractice and Surgery of the Thyroid and Parathyroid Glands / Daniel D Lydiatt, Robert Lindau -- Extent of Thyroidectomy and Incidence of Morbidity / Dana M Hartl, Martin Schlumberger -- Thyroid Surgery in Paediatric Patients / Scott A Rivkees, Christopher K Breuer, Robert Udelsman -- Best Practices in Thyroid Surgery. How to Perform a "Safe" Thyroidectomy / Elliot J Mitmaker, Quan-Yang Duh -- Minimally Invasive Video-assisted Thyroidectomy / Paolo Miccoli, Michele N Minuto, Piero Berti -- Robotic Thyroid Surgery / Michael C Singer, David J Terris -- Extensive Surgery for Thyroid Cancer / Emad H Kandil, Salem I Noureldine, Ralph P Tufano -- Extensive Surgery for Thyroid Cancer / Dana M Hartl, Haitham Mirghani, Daniel F Brasnu -- Surgery for Retrosternal/Upper Mediastinal Thyroid/Parathyroid Disease / Jeffrey J Houlton, David L Steward -- Reoperative Thyroid Surgery / N Gopalakrishna Iyer, Ashok R Shaha -- How to Use Energy Devices and their Potential Hazards / Paolo Miccoli, Michele N Minuto -- Intraoperative Complications. The Recurrent Laryngeal Nerve / David Goldenberg, Gregory W Randolph -- The Superior Laryngeal Nerve / Tammy M Holm, Sara I Pai -- The Parathyroid Glands in Thyroid Surgery / Maisie Shindo -- Cosmetic Complications / Melanie W Seybt, David J Terris -- Intraoperative Complications. Management and Prevention of Laryngotracheal and Oesophageal Injuries in Thyroid Surgery / Eran E Alon, Mark L Urken -- Injury of the Major Vessels / Lourdes Quintanilla-Dieck, Neil D Gross -- Lesions Following Lateral Neck Dissection / Clive S Grant -- Amiodarone-induced Thyrotoxicosis and Thyroid Storm / Fausto Bogazzi, Luca Tomisti, Piero Berti, Enio Martino -- Postoperative Complications Requiring Urgent Treatment. Respiratory Failure Following Extubation / Moran Amit, Dan M Fliss -- Postoperative Bleeding / Richelle T Williams, Peter Angelos -- The Occurrence and Management of Pneumothorax in Thyroid Surgery / Kamran Samakar, Jason Wallen, Alfred Simental -- Postoperative Complications. The Recurrent Laryngeal Nerve / Michele P Morrison, Gregory N Postma -- The Parathyroids / Claudio Marcocci, Luisella Cianferotti -- The Rare Ones: Horner's Syndrome, Complications from Surgical Positioning and Post-Sternotomy Complications / Lukas H Kus, Jeremy L Freeman -- Late Complications of Thyroid Surgery / Dennis R Maceri -- Post-thyroidectomy Distress / Mira Milas, Zvonimir Milas -- New Issues: Complications Following Minimally Invasive and Robotic Techniques. Minimally Invasive Techniques Performed Through the Neck Access / Paolo Miccoli, Michele N Minuto, Valeria Matteucci -- Minimally Invasive Techniques Performed Through Other Accesses / Kee-Hyun Nam, William B Inabnet -- Complications of Robotic Thyroidectomy / David J Terris, Michael C Singer -- Iatrogenic Hypothyroidism, Metabolic Effects of Post-thyroidectomy Thyroid Hormone Replacement, and Quality of Life after Thyroid Surgery. Iatrogenic Hypothyroidism and Its Sequelae / Paolo Vitti, Francesco Latrofa -- Quality of Life after Thyroid Surgery / Alessandro Antonelli, Poupak Fallahi.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Thyroid gland -- Surgery -- Complications; Electronic books